BENTUK IMPLIKATUR PERCAKAPAN PADA UNGKAPAN PEMBERLAKUAN KURIKULUM 2013 DI SMK N 8 SURAKARTA - Hari Prayogo; Atiqa Sabardila (Jurnal Penelitian Humaniora, 2016)
This research aims to describe the form of implicatures found in conversations between students and teachers based on the implementation of the 2013 Curicullum enactment in SMK N 8 Surakarta. This research is qualitative type which also uses thedescriptive method within it. The data sources of this research are the conversations between students and teachers. The samples of this research are expression of the 2013 curicullum 2013’s enactments in SMK N 8 Surakarta. The data collecting technique in this research is attentive method followed by quotation method. The analysis technique is the selection elements determined by the selection of pragmatic.Also, this research uses an advancing step that is connect-compare with the standard variety. The results can be clarified in eight types. They are (1) implicature with the intention to explain, (2) implicature with the intention of complaining, (3) implicaturewith intention of asking, (4) implicature with intention to satirize, (5) implicature with the intention of the prediction, (6) implicature with the intention of the skepticism (7) implicature with the intention of the are a speeches and (8) implicature with the intention of the appealing.